Phase separated nanofibrous anion exchange membranes with polycationic side chains - Abouzari-Lotf, E. (Royal Society of Chemistry, 2017)
Anion exchange membranes (AEMs) have gained significant interest in electrochemical energy devices with a unique set of benefits. However, none of the commercial AEMs behave ideally under alkaline operation conditions and developing appropriate membranes is one of the major hurdles to the durability and performance of anion exchange membrane fuel cells. Here we demonstrate a simple and efficient strategy of using nanofibrous materials, activated by radiation and functionalized with ionic groups to fabricate highly durable and conductive membranes with polycationic side chains. Two series of AEMs were prepared by radiation induced emulsion grafting of vinylbenzyl chloride onto syndiotactic polypropylene and nylon-66 nanofibrous sheets followed by crosslinking and introducing quaternary ammonium groups. A strong correlation was found between the choice of nanofibrous substrate as well as crosslinking degrees with water uptake, ion conductivity and stability of the membranes. A well-developed phase separated morphology was confirmed and the membranes with ion exchange capacities of 1.6-2.1 mmol g-1 showed high ionic conductivity, low methanol permeability and excellent alkaline stability. A hydroxide ion conductivity as high as 132 mS cm-1 was achieved at 80 °C and it was exceptionally retained at up to 90 after evaluation by accelerated degradation testing in 1 M NaOH at 80 °C for 672 h. A Pt-catalyzed fuel cell using these nanofibrous composite membranes showed a peak power density of above 120 mW cm-2 at 80 °C under 90 relative humidity. This strategy and observed properties pave the way for highly conductive and durable ion conducting membranes with tunable characteristics. © 2017 The Royal Society of Chemistry.